Immunotherapy to Avoid Orbital Exenteration in Patients With Cutaneous Squamous Cell Carcinoma - McLean, Luke S.; Lim, Annette M.; Webb, Angela; Cavanagh, Karda; Thai, Alesha; Magarey, Matthew; Fox, Carly; Kleid, Stephen; Rischin, Danny (Frontiers in Oncology, 2022)
Background Cutaneous squamous cell carcinoma (CSCC) of the head and neck can require complex and disfiguring surgery in order to achieve cure, which can be morbid and negatively impact patient quality of life. The management of advanced CSCC has been revolutionized by immunotherapy with current clinical trials also exploring its role in the neoadjuvant and adjuvant settings. Patients may decline morbid curative surgery, such as orbital exenteration, and the outcomes of immunotherapy use in this unique group of patients requires further investigation. Methods We reviewed the records of 119 patients treated at a major Australian quaternary oncology centre with immunotherapy (either cemiplimab or pembrolizumab) for advanced CSCC. Results We identified 7 patients recommended curative surgery involving orbital exenteration after multidisciplinary discussion, who, declined surgery due to concerns about morbidity and/or disfigurement. All 7 patients demonstrated a response to treatment and six avoided orbital exenteration. Two patients experienced pseudoprogression. Conclusions The management of CSCC can be complex and requires the input of a multidisciplinary team. Immunotherapy to avoid or reduce the extent of morbid definitive surgery is an emerging treatment option.